(untitled) (Jurnal Adabiya, 2023)
This study discusses the comparative effectiveness of the Yogyakarta city library drive-thru service and the Kuala Lumpur city library during the Covid-19 pandemic. This study aims to find out and describe the effectiveness of the use of drive-thru services in Yogyakarta city libraries and Kuala Lumpur libraries during the Covid-19 pandemic. This research involved field research using descriptions for quantitative research with a special focus on the research concerned. To collect information, researchers used observation questionnaires, interviews, and documentation. The sample size for this study was 65,628, and 133 respondents were randomly selected from the group using the Slovin survey. Data analysis uses the grand mean and mean formula. The results of data collection in the field can be seen that 4 indicators namely service, borrowing, returning, as well as indicators of user perceptions of librarians obtain a total value of 81.53%. So it can be concluded that the results of the overall calculation of respondents’ answers, namely the effectiveness of drive-thru services in libraries at the Yogyakarta City Library and Kuala Lumpur Library during the Covid-19 pandemic were classified as very good.